Characterizing axial crash foldability of AHSS & UHSS sheets by means of L-profile compression tests. (November 2019) - Wagner, L.; Larour, P.; Lackner, J.; Schauer, H.; Berger, E.
Abstract: Small-scale crash tests of crash boxes have established themselves as an assessment tool for high strength materials for their application in crash-relevant structures in the automotive body. However, when investigating UHSS grades it can be seen that the performance outcome is highly susceptible to details of the crash box geometry, e.g. shape of cross section or position of spot welds, and the test setup. This may even lead to opposing crash performance ratings for the same grade if different setups are compared. In order to rule out any side effects of specimen geometry and test setup, a simpler test method is desired. If a crash box sustains plastic folding in its first fold it often also sustains the subsequent plastic folding events. Accordingly, the L-profile compression test is presented where a specimen, mimicking a quarter of the crash box cross-section, is compressed, forming a single plastic fold. The crash performance assessment is carried out by means of the so called crash index, a weighted relative measure of crack and fracture lengths within the sample, and correlated to the results of corresponding small scale tests, i.e. bending, notched tensile and hole expansion tests.